Estresse celular para a produção de biocompostos em Spirulina platensis - Zaparoli, Munise (2019)
The production of renewable biofuel in microalgae based biorefinery have receive attention as potential energy sources for the future. The need to replace the energy matrix and reduce impacts of non-renewable raw materials on global warming and climate change increase the necessity of new renewable fuels. Studies have been conducted with microalgae due to their short growing time, plus they are abundant raw materials and use as growth energy CO2 (greenhouse gas) and solar energy. The microalgae biomass can easily accumulate intracellular carbohydrates, which can be used in bioethanol production, biokeresone, biogas, and other biofuels. The stimulation of environmental and nutritional stress allows changes in the microalgae metabolic routes, causing carbohydrates to accumulate in energy form, increasing productivity. Also, high-value coproducts can be created to increase the economical level of microalgae biorefineries, such as biosurfactants. This study goal is to increase the synthesis of extracellular carbohydrates and biosurfactants from the Spirulina platensis by nutritional and physical stresses. Spirulina platensis was cultivated in two steps. In the first step, nutrient -rich medium (50% Zarrouk‟s medium ) was used, allowing cyanobacteria growth until the end of the exponential growth phase (18° d). In the second step, the gowned cells were centrifuged and recycled in a new growth medium (20% Zarrouk‟s medium), and subjected to physical stresses (UV radiation, photoperiod/luminosity, NaCl, hydrogen peroxide), nutritional stresses (shortage or enrichment of Ca, Fe and Mg concentrations in 20% Zarrouk‟s medium ). All stress conditions were performed in duplicate and with three concentration levels over 15 days (Stage II). At the end, intracellular production of carbohydrates, proteins and extracellular biosurfactants were analyzed. The best results were selected for a combining stress approach. Therefore, a 2 2 factorial design was made. The stresses with the highest carbohydrate productivities in the first stage of the two stage culture study was 300 mM NaCl (10.27 mg.L -1 .d -1 ), with UV radiation 6 min (9.80 mg.L -1 .d -1 ), Mg 0.01 g.L -1 (9.75 mg.L -1 .d -1 ) and 18h/06h photoperiod of 67.5 μmol photons m -2 .s -1 (27.84 mg.L -1 d -1 ). The biosurfactants quantification from the reduction of surface tensions was identified in all the calcium supplementation cultures. The development of stable emulsions was only verified under photoperiod/light intensity stress conditions. The nutrient restriction by 20% Zarrouk‟s medium , combined with higher light intensity and photoperiod shown to be an efficient strategy to achieve higher intracellular concentrations (59 .71%) and carbohydrate productivities (55.85 mg.L -1 .d -1 ) in a single cultivation stage.